Surgical Reconstruction Options in Chronic Distal Biceps Tendon Ruptures - Case Report and Literature Review. - Riesner, Hans-Joachim; Hackenbroch, Carsten; Lang, Patricia; Achatz, Gerhard; Palm, Hans-Georg; Friemert, Benedikt (Zeitschrift für Orthopädie und Unfallchirurgie, 2021)
INTRODUCTION: Chronic distal biceps tendon ruptures are rare and conservative or operative treatment options are suitable. There is a consensus in the literature in case of acute traumatic ruptures the operative refixation should be preferred. Disagreement exists in the best way of care of old ruptures (> 4 weeks) of distal biceps tendon. Several kinds of refixation possibilities up to tendon grafts are described. Aim of this publication is showing an overview of the literature of the approved methods in reconstruction of the distal biceps tendon using autogenous and allogenic grafts, comparing the outcomes and transferring them on an own case. MATERIAL AND METHODS: A literature research was carried out using the online medical database "PubMed" with the following keywords "chronic rupture distal biceps tendon, surgical techniques". 59 citations were found concerning the topic, 37 publications were relevant for this work. RESULTS: There is consensus that even in chronic ruptures the operative management of the distal biceps tendon generates the best results. Consistently the experiences and results of only little patient collectives are reported. Numerous techniques of surgery are described without predominance of one method. Reinsertions of the tendon butts are reported in different techniques: with achilles, palmaris longus, fascia lata, triceps, quadriceps and semitendinosus tendon grafts. All together they showed postoperative satisfactory results. CONCLUSION: With surgical treatment of chronic ruptured distal biceps tendons comparable outcomes can be achieved by primary refixation and graft augmentations. In case of graft augmentations several tissue options are available which showed in all cases satisfactory functional results in the end.
EVALuna2:529620